Kindergarten Teachers' Perceptions of the Limited Face-to-Face Group Learning Model - Umi - Hani (AWLADY : Jurnal Pendidikan Anak, 2022)
ABSTRACTThe new transition period after the COVID-19 pandemic demands the implementation of learning with new provisions. Limited face-to-face learning is one of the options for implementing learning in PAUD units which is carried out through a group learning model approach. The purpose of this study was to describe PAUD teachers' perceptions of the limited face-to-face group learning model. Information about teacher perceptions was obtained through questions about school policy, experience, efficiency, supporting factors and obstacles in the group learning model presented through case studies using a qualitative approach. The research subjects involved 6 teachers who served in five kindergartens in the city of Yogyakarta. The results of the study found that the group learning model is an appropriate and fun policy, provides space for children to socialize, meet face-to-face, is able to limit the crowd and reduce the burden on parents in assisting learning at home, effective in monitoring children's development, conditioning children and easy knowledge. absorbed, as well as maximum support from school residents, parents, local residents, the COVID-19 task force and the police. The obstacles found were disciplining children in complying with health protocols, lack of time in giving stimulation, limited children in playing, sterilizing the school environment and the efficiency of increasing maintenance operational costs.Keywords: Teacher perception, group learning model, limited face-to-face